The Effect of Hyperuricemia on the Rate of Contrast-Induced Nephropathy in Patients with Coronary Angiography - Hossein Vakili; Sara Chaghazardi; Isa Khaheshi; Mohammadreza Naderian (International Journal of Cardiovascular Practice, 2016)
Introduction: There is little information about the relationship between hyperuricemia and contrast induced nephropathy. The present study aimed to evaluate the relationship between hyperuricemia and contrast induced nephropathy among patients, who had undergone coronary angiography.Methods: In the current study, 200 consecutive patients with coronary artery disease, who underwent coronary angiography in Modarres hospital, were enrolled. According to the available data, the upper limit normal level of uric acid was defined as 7 mg/dl in males and 6.5 mg/dl in females. By increasing level of serum creatinine to 0.5 mg/dl (or 25% enhancement) from basic level of creatinine during 48 hours of introduction of contrast agent, diagnosis of Contrast Induced Nephropathy (CIN) was established. The relationship between hyperuricemia and CIN was then assessed.Results: There is a significant difference between normouricemic patients and hyperuricemic patients, in aspect of weight (P = 0.011) and uric acid (P = 0.001); however, other quantitative and qualitative variables including age, volume of contract agent, creatinine level after angiography, hemoglobin level, gender, arterial access type, number of involved vessels, were insignificant between the two groups (P > 0.05). Moreover, as an essential finding, CIN was shown in 9% of normouricemic patients and 10% of hyperuricemic  patients with no significant difference between the two groups (P = 0.6).Conclusions: Our study suggests that hyperuricemia may not significantly increase the rate of the contrast-induced nephropathy in patients, who had undergone angiography